2002
DOI: 10.1007/s00421-002-0682-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water ingestion on cardiovascular and thermal responses to prolonged cycling and running in humans: a comparison

Abstract: The aim of this investigation was to examine the effect of water ingestion on physiological responses to prolonged cycling (CYC) and running (RUN). A group of 11 men with mean (SEM) maximal oxygen uptake (VO(2max)) 48.5 (1.8) ml x kg(-1) x min(-1) on a cycle-ergometer and 52.1 (2.2) ml x kg(-1) x min(-1) on a treadmill (P<0.01) exercised for 90 min on four occasions, twice on each ergometer, at 60% of mode specific VO(2max). No fluid was taken (D) in one trial on each ergometer, whereas 60% of fluid losses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
1
3
1
1
Order By: Relevance
“…alez-Alonso et al, 1997). However, the present heart rate results are not unlike those reported by Nassis and Geladas (2002) who found no differences in heart rate response over 90 min of cycling exercise with and without dehydration. These authors made the point that fluid ingestion might not induce tachycardia until at least 100 min of exercise as shown in other studies (Montain and Coyle, 1992b;McConell et al, 1997;Fallowfield et al, 1996;Hamilton et al, 1991;Galloway and Maughan, 2000).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…alez-Alonso et al, 1997). However, the present heart rate results are not unlike those reported by Nassis and Geladas (2002) who found no differences in heart rate response over 90 min of cycling exercise with and without dehydration. These authors made the point that fluid ingestion might not induce tachycardia until at least 100 min of exercise as shown in other studies (Montain and Coyle, 1992b;McConell et al, 1997;Fallowfield et al, 1996;Hamilton et al, 1991;Galloway and Maughan, 2000).…”
Section: Discussioncontrasting
confidence: 84%
“…However, the present findings are not completely dissimilar to those of McConell et al (1997) that rectal temperature was not different up to 60 min of exercise in a moderate environment (21 C) when subjects ingested either no fluid, half the fluid equal to sweat rates or fluid equal to sweat rates. More recently, 90 min of cycling exercise with and without dehydration did not result in any significant differences in rectal temperature (Nassis and Geladas, 2002). In the present study, the rectal temperature was similar between hydration conditions at the end of 40 min of exercise, even though the exercise was discontinuous and the environmental conditions were warm and humid.…”
Section: Discussionsupporting
confidence: 51%
“…The observed decrease in heart rate in the present study represents a physiological change that may have contributed in improving performance. It has been shown that reducing exercise-induced dehydration during prolonged cycling in a temperate climate, as pre-exercise hyperhydration allowed in the current study, is associated with a reduction in heart rate and an increase in plasma volume, stroke volume and cardiac output (Hamilton et al, 1991;Nassis et al, 2002). If in the present study cardiac output was indeed enhanced with pre-exercise hyperhydration, then it could have contributed to the increase in endurance capacity by improving oxygen and nutrient delivery to the muscle, waste removal and buffering capacity (Casa, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…During exercise, hyperthermia could distribute more blood for peripheral convective cooling and augment sweat loss for evaporative cooling (Reilly et al, 2006), which impaired exercise capacity (Nybo, 2008). Furthermore, the augmented sweat loss could induce a progressive decrease in body fluids and lead to dehydration (Nassis and Geladas, 2003a;Nassis and Geladas, 2003b;Quod et al, 2006). A low degree of dehydration could impair thermoregulatory function and aggravate cardiovascular strain (Kenefick, 2018).…”
Section: Introductionmentioning
confidence: 99%